Exploration of Innovative New Paths for Intelligent Empowerment in Software Testing and Evaluation - Jiang, Dinggui (Innovative Applications of AI, 2025)
With the vigorous development of the software industry, the complexity of software systems is increasing day by day, and the shortcomings of traditional software testing and evaluation methods in terms of efficiency and accuracy have become more apparent. This paper focuses on the field of intelligent empowerment in software testing and evaluation, delving into innovative paths. By constructing an intelligent empowerment framework for software testing and evaluation, it elaborates on its core modules and the principles of embedding intelligent technologies, and conducts argumentation and analysis with actual cases. The research indicates that intelligent empowerment can significantly enhance the efficiency and quality of software testing and evaluation, injecting new momentum into the development of the software industry, while also pointing the way for future research and practice in the field.